How to Write a Collaboration Plan - Kara L. Hall; Kevin Crowston; Amanda L. Vogel (Team Science Toolkit, 2014)
Collaboration plans are written documents that investigators may use as a “roadmap” for future collaborations. Funding agencies may ask investigators to submit Collaboration Plans as part of their funding applications, analogous to submitting research plans. Submitted collaboration plans can then be used by reviewers to help assess the capacity of a proposed team to collaboratively execute its scientific objectives. Collaboration plans address a range of issues relevant to laying the foundation for the collaboration, implementing and managing the collaboration, and engaging in quality improvement activities specific to collaborative interactions. These plans identify existing supports and challenges relevant to the collaboration, and describe a program of action that will be implemented to help support smooth collaboration. This working document, called “How to Write a Collaboration Plan” is a product of a federal subcommittee on Collaboration and Team Science. The document provides guidance for writing a collaboration plan. It identifies ten key aspects of collaboration planning, and highlights specific issues for investigators to consider related to each of the ten aspects of planning. Collaboration planning may benefit any scientific endeavor that includes two or more investigators working together. Though as a proposed scientific collaboration grows in scope and size, such plans become increasingly important. More information on the origins of this document: The White House Office of National Science and Technology Policy’s (OSTP) NITRD Program (Networking and Information Technology Research and Development Program) provides a forum where many federal agencies come together to coordinate their networking and information technology (IT) research and development (R&D) efforts. (More information at: https://www.nitrd.gov.) Team Science is of particular interest, given the prevalence of virtual collaboration in IT R&D. In response, the NITRD Coordination Group on Social, Economic, and Workforce Implications of IT and IT Workforce Development (NITRD-SEW), developed a subcommittee on Collaboration and Team Science. The subcommittee includes members from the National Institutes of Health (NIH), National Science Foundation (NSF), Department of Justice (DOJ), NASA, and other federal agencies. In 2014, the subcommittee hosted a series of topical meetings on enhancing support for collaboration in science, which resulted in this document, “How to Write a Collaboration Plan”, authored by subcommittee co-chairs Dr. Kara Hall (NIH) and Dr. Kevin Crowston (NSF), along with subcommittee member Dr. Amanda Vogel (Leidos Biomed).